A novel missense variant in SLC18A2 causes recessive brain monoamine vesicular transport disease and absent serotonin in platelets. Issue 1 (25th March 2019) - Padmakumar, Manisha; Jaeken, Jaak; Ramaekers, Vincent; Lagae, Lieven; Greene, Daniel; Thys, Chantal; Van Geet, Chris; BioResource, NIHR; Stirrups, Kathleen; Downes, Kate; Turro, Ernest; Freson, Kathleen
Abstract: Background: Brain monoamine vesicular transport disease is an infantile onset neurodevelopmental disorder caused by variants in SLC18A2, which codes for the vesicular monoamine transporter 2 (VMAT2) protein, involved in the transport of monoamines into synaptic vesicles and of serotonin into platelet dense granules. Case presentation: The presented case is of a child, born of healthy consanguineous parents, who exhibited hypotonia, mental disability, epilepsy, uncontrolled movements, and gastrointestinal problems. A trial treatment with L‐DOPA proved unsuccessful and the exact neurological involvement could not be discerned due to normal metabolic and brain magnetic resonance imaging results. Platelet studies and whole genome sequencing were performed. At age 4, the child's platelets showed a mild aggregation and adenosine triphosphate secretion defect that could be explained by dysmorphic dense granules observed by electron microscopy. Interestingly, the dense granules were almost completely depleted of serotonin. A novel homozygous p.P316A missense variant in VMAT2 was detected in the patient and the consanguineous parents were found to be heterozygous for this variant. Although the presence of VMAT2 on platelet dense granules has been demonstrated before, this is the first report of defective platelet dense granule function related to absent serotonin storage in a patient with VMAT2 deficiency but without obvious clinical bleeding problems. Conclusions: This study illustrates the homology between serotonin metabolism in brain and platelets, suggesting that these blood cells can be model cells for some pathways relevant for neurological diseases. The literature on VMAT2 deficiency is reviewed.